Postharvest oxidative stress in plums : mechanism and implications for storage and fruit quality - Singh, Sukhvinder Pal (Curtin University, 2010)
Postharvest life and susceptibility to chilling injury (CI) in Japanese plums (Prunus salicina Lindl.) are greatly influenced by preharvest and postharvest factors. The phenomenon of postharvest oxidative stress has been implicated in affecting fruit quality, potential storability and susceptibility to development of physiological disorders during storage of fruits. Therefore, the investigations were carried out to understand the role of various factors, such as cultivar, harvest maturity, storage conditions (temperature and atmosphere composition), duration of storage and postharvest treatments, in the development of oxidative stress in Japanese plums, in relation to fruit quality and CI. The degree of lipid peroxidation and membrane integrity was measured by determining the activity of lipoxygenase enzyme, concentration of thiobarbituric acid–reactive substances, and amount of electrolyte leakage. The activities of antioxidant enzymes, superoxide dismutase, catalase, and peroxidase, were determined as a direct measure of the enzymatic antioxidant capacity. The activities of enzymes (ascorbate peroxidase, monodehydroascorbate reductase, dehydroascorbate reductase, glutathione reductase, and glutathione–S–transferase) involved in the oxidation and regeneration of ascorbate (AA) and glutathione (GSH) were also determined to underpin the dynamics of the AA–GSH cycle. The concentrations of AA, dehydroascorbate (DHA), GSH, and oxidized glutathione (GSSG) were determined to compute the AA:DHA and GSH:GSSG ratios as the indicators of redox potential of fruit tissue. The total phenolics concentration and total antioxidant capacity were also determined as a part of the non–enzymatic antioxidants.The experimental data suggest that postharvest oxidative stress developed during fruit ripening in Japanese plums, but the rate was dependent on the climacteric behaviour of fruit. The climacteric cultivars, ‘Blackamber’ and ‘Amber Jewel’, showed a faster decline in the ability of antioxidative system to encounter the oxidative stress during fruit ripening as compared to ‘Angeleno’, a suppressed–climacteric cultivar. The delay in harvesting of ‘Amber Jewel’ plums by one week slightly improved fruit quality and the initial status of antioxidants than the commercial harvest. However, the fruit harvested at commercial maturity had better retention of antioxidative system during cold storage at 0°C for 3–4 weeks compared to the fruit from the delayed harvest. The changes in enzymatic and non–enzymatic antioxidants as a function of storage duration appear to be more prominent in providing protection against oxidative injury expressed as CI than their at–harvest status. The response of the antioxidative system in ‘Amber Jewel’ plums at 5°C was significantly better than at 0°C. But, the storage temperature of 5°C was not sufficiently low to inhibit the process of fruit ripening, resulting in limited storage life of 2 weeks. The multiple–point time course analysis of lipid peroxidation and changes in enzymatic and non–enzymatic antioxidants of ‘Blackamber’ plums revealed that the third week of storage is the critical point beyond which the capacity of antioxidative system to cope with the increasing oxidative stress from CI and fruit ripening began to decline, resulting in increased incidence and severity of CI during the extended periods of storage. Controlled atmospheres (CA) were found beneficial to reduce the levels of oxidative stress in ‘Blackamber’ plums.CA containing 1% O[subscript]2 + 3% CO[subscript]2 were effective in mitigating the oxidative stress during the 5 weeks of cold storage at 0–1°C, plus 6 days of shelf life at 21±1°C. The efficacy of CA (1% or 2.5% O[subscript]2 + 3% CO[subscript]2) in alleviating CI in ‘Blackamber’ plums could be further enhanced by the pre–storage treatment of fruit with 1–methylcyclopropene (1–MCP, 0.6 μL L[superscript]–[superscript]1). The combination of CA and 1–MCP exhibited synergistic effects on the alleviation of oxidative stress, resulting in enhanced storage life up to 8 weeks, plus 6 days of shelf–life. The role of nitric oxide (NO) as an antioxidant was also investigated in order to retard fruit ripening, delay the onset of senescence and development of oxidative stress in the Japanese plums. Postharvest NO fumigation (10 or 20 μL L[superscript]–[superscript]1) delayed the fruit ripening and maintained quality for 9–12 days in ‘Amber Jewel’ and ‘Blackamber’ plums at 21±1°C. NO fumigation was also beneficial to reduce the symptoms of CI during cold storage of ‘Amber Jewel’ and ‘Blackamber’ plums for 5–6 weeks at 0°C, plus 5 days of shelf–life at 21±1°C. The positive effects of NO fumigation on the enzymatic and non–enzymatic antioxidants in addition to reduced rates of lipid peroxidation were associated with the enhanced chilling tolerance in Japanese plums. The response of ‘Amber Jewel’ to postharvest NO fumigation was significantly better than ‘Blackamber’.In conclusion, the development of oxidative stress in Japanese plums was influenced by cultivar, harvest maturity, cold storage (temperature, duration and atmosphere composition), and postharvest treatments with NO and 1–MCP. The mitigation of oxidative stress by manipulation of postharvest storage conditions and treatments can be achieved to maintain fruit quality and reduce the incidence and severity of CI in Japanese plums.